9 Using what people value to develop new interventions in palliative care: a multilevel level review approach. Issue 3 (1st September 2018) - Candy, B; Armstrong, M; Amey, R; Booth, J; Flemming, K; Kupeli, N; Maclean, V; Preston, J; Stone, P; Wilkinson, S
Abstract : Introduction: Complex interventions are common in palliative care (PC) but are difficult to evaluate. Complementary therapies (CT) are one type of widely-used complex intervention for which there is inconclusive evidence. No systematic review has been conducted in PC of trials or of qualitative studies of patients' views of CTs. There are novel approaches with established exemplars of using both types of reviews to help develop more clinically appropriate interventions. These approaches are in their infancy in PC research and have much to offer the specialism. Aims: Using our on-going review on CT we present as an exemplar in PC an approach to draw together the findings of trials and qualitative studies in a data table (matrix) to contrast what patients value and want with how the intervention is tested. Methods: We sought trials on the effectiveness of CT and qualitative studies on patients' perspectives about these therapies. Our primary outcomes for trials included anxiety. Eight databases were searched in 2017. Citations and full-text papers were reviewed to identify relevant studies. Meta-analyses pooled trial data where appropriate and a thematic synthesis is being undertaken to understand patient experience. These findings will be combined in a matrix to explore similarities and differences. Results: 19 trials and five qualitative studies were included. Data analysis and development of the matrix which includes intervention content and patients' needs is currently underway. We will present the final matrix framework. Conclusions: Our approach demonstrates a potential way in PC to enhance development of practice appropriate complex interventions.